REKONSTRUKSI METODOLOGI EVALUASI MAKRO: OPTIMALISASI STATISTIK DESKRIPTIF DALAM MENAKAR CAPAIAN KARAKTER PADA PEMBELAJARAN PAI KONTEMPORER - Muhammad Roziq Syafi'ul Umam; Muhammad Adhib Assholih; Suhaimi Ahmad Muntaha; M. Aidhil Adhan; Nugroho Prasetya Adi (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2025)
The modernization of education necessitates profound reform in the assessment systems for Islamic Religious Education (PAI) to move away from evaluation patterns marred by subjectivity and personal bias. The dominance of conventional qualitative assessments which rely heavily on educators' intuition often hinders the macro-level and collective mapping of instructional quality. This study aims to examine the optimization of basic descriptive statistics specifically measures of central tendency such as the mean, median, and mode as instruments for macro-level evaluation in contemporary PAI. Employing a library research method with a descriptive-qualitative approach, the study reveals that the application of descriptive statistics is not merely a process of reducing numerical data; rather, it serves as an educational diagnostic tool capable of mapping on a class wide basis student achievement across the dimensions of ta’lim (cognitive aspects), tarbiyah (psychomotor aspects/potential), and ta’dib (affective aspects/character). Integrating descriptive statistics into the realm of PAI represents a concrete manifestation of the tradition of scholarly verification (tabayyun), equipping educators with a valid data foundation to formulate instructional policies and accurately reinforce the orientation of moral education.